Hepatitis C Virus Entry Is Impaired by Claudin-1 Downregulation in Diacylglycerol Acyltransferase-1-Deficient Cells - Sung, Pil Soo (American Society for Microbiology, 2014)
Diacylglycerol acyltransferase-1 (DGAT1) is involved in the assembly of hepatitis C virus (HCV) by facilitating the trafficking of the HCV core protein to the lipid droplet. Here, we abrogated DGAT1 expression in Huh-7.5 cells by using either the transcription activator-like effector nuclease (TALEN) or lentivirus vector short hairpin RNA (shRNA) and achieved complete long-term silencing of DGAT1. HCV entry was severely impaired in DGAT1-silenced Huh-7.5 cell lines, which showed markedly diminished claudin-1 (CLDN1) expression. In DGAT1-silenced cell lines, the forced expression of CLDN1 restored HCV entry, implying that the downregulation of CLDN1 is a critical factor underlying defective HCV entry. The expression of the gene coding for hepatocyte nuclear factor 4α (HNF4α) and other hepatocyte-specific genes was also reduced in DGAT1-silenced cell lines. After DGAT1 gene rescue, CLDN1 expression was preserved, and HCV entry was restored. Strikingly, after DGAT1 silencing, CLDN1 expression and HCV entry were also restored by low-dose palmitic acid treatment, indicating that the downregulation of CLDN1 was associated with altered fatty acid homeostasis in the absence of DGAT1. Our findings provide novel insight into the role of DGAT1 in the life cycle of HCV. IMPORTANCE In this study, we report the novel effect of complete silencing of DGAT1 on the entry of HCV. DGAT1 was recently reported as a host factor of HCV, involved in the assembly of HCV by facilitating the trafficking of the HCV core protein to lipid droplets. We achieved complete and long-term silencing of DGAT1 by either TALEN or repeated transduction of lentivirus shRNA. We found that HCV entry was severely impaired in DGAT1-silenced cell lines. The impairment of HCV entry was caused by CLDN1 downregulation, and the expression of HNF4α and other hepatocyte-specific genes was also downregulated in DGAT1-silenced cell lines. Our results suggest new roles of DGAT1 in human liver-derived cells: maintaining intracellular lipid homeostasis and affecting HCV entry by modulating CLDN1 expression.